The Impact of Top-Down Prediction on Emotional Face Processing in Social Anxiety - Ran, Guangming; Chen, Xu (Frontiers in Psychology, 2017)
There is evidence that people with social anxiety show abnormal processing of emotional faces. To investigate the impact of top-down prediction on emotional face processing in social anxiety, brain responses of participants with high and low social anxiety were recorded, while they performed a variation of the emotional task, using high temporal resolution event-related potential techniques. Behaviorally, we reported an effect of prediction with higher accuracy for predictable than unpredictable faces. Furthermore, we found that participants with high social anxiety (HSA), but not with low social anxiety (LSA), recognized angry faces more accurately than happy faces. For the P100 and P200 components, HSA participants showed enhanced brain activity for angry faces compared to happy faces, suggesting a hypervigilance to angry faces. Importantly, HSA participants exhibited larger N170 amplitudes in the right hemisphere electrodes than LSA participants when they observed unpredictable angry faces, but not when the angry faces were predictable. This probably reflects the top-down prediction improving the deficiency at building a holistic face representation in HSA participants.